PEMBANGUNAN JALAN TOL DI INDONESIA: KENDALA PEMBEBASAN TANAH UNTUK PEMBANGUNAN BAGI KEPENTINGAN UMUM DAN GAGASAN UPAYA PENYELESAIANNYA - Senthot Sudirman (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
The study is aimed at (a) identifying both legal and empirical constraints inhibiting the process of land clearing whichis one the important factors in land acquisition for public facilities, and (b) suggesting the concept of solving the problem, especiallyon the construction of Trans Java toll road. The research is done by library studies including legislations, documents, interviews.The efforts to solve the problems on land clearance was based on academic studies using references such as books, legislations,empirical and data and facts and actors opinions. Several constraints already identified are: (a) the difficulty of achieving anagreement on the amount of compensation caused by (i) the minimum knowledge awareness on the social function of land (ii) theimportance of infrastructure building, including toll roads, (iii) the limited fund for land acquisition, (iv) the dispute on landownership, (v) the existence of land acquisition objects by BUMN, BUMD and wakaf land, (b) the incomplete file on landacquisition, (c) the invalid evidence of land ownership, (d) the presence of land speculators, (e) the presence of provocateurs (f) theweek cooperation of private-state scheme, etc.Keywords: constraints, land clearance, land acquisition, public facilities.